Implementasi Critical Care Outreach Team (CCOT) di Rumah Sakit Sentra Medika Minahasa Utara - Watuna, Monica C.; Lantang, Eka Y. (Universitas Sam Ratulangi, 2026)
Abstract: Clinical deterioration among hospitalized patients often occurs suddenly and can be prevented through early identification and timely intervention. The Critical Care Outreach Team (CCOT), as part of the Rapid Response System (RRS), is designed to detect and manage clinical deterioration before patients require admission to the Intensive Care Unit (ICU). This study aimed to describe the implementation of CCOT at Sentra Medika Hospital, North Minahasa, during the period from August 2024 to August 2025. A descriptive observational design was employed, with the researcher acting as a non-participant observer. Data collected included patient demographics, Early Warning Score (EWS) at admission and discharge, and the effectiveness of CCOT interventions based on patient stability, ICU readmission, code blue events, and mortality. Among 136 monitored patients, the highest proportion (30.8%) were aged 56–65 years and presented with moderate to high EWS upon admission. Following CCOT intervention, the average EWS decreased from 5.9 to 4.5. A total of 94.1% of patients remained stable in the ward, 3.7% were readmitted to the ICU, 1.5% experienced code blue events, and 0.7% died. In conclusion, the implementation of CCOT at this hospital has proven effective in the early detection of clinical deterioration and timely intervention, contributing to improved patient safety and service efficiency. Keywords: Early Warning Score (EWS); Rapid Response System (RRS); Critical Care Outreach Team (CCOT); clinical deterioration; early intervention Abstrak: Kemunduran kondisi pasien rawat inap sering kali terjadi secara tiba-tiba dan dapat dicegah melalui identifikasi dini serta intervensi cepat. Critical Care Outreach Team (CCOT) merupakan bagian dari sistem Rapid Response System (RRS) yang bertujuan mendeteksi dan menangani kemunduran kondisi sebelum pasien membutuhkan perawatan di Intensive Care Unit (ICU). Penelitian ini bertujuan untuk memberikan gambaran implementasi CCOT di Rumah Sakit Sentra Medika Minahasa Utara selama periode Agustus 2024 hingga Agustus 2025. Metode penelitian menggunakan desain deskriptif observasional. Peneliti berperan sebagai pengamat yang mencatat data demografis pasien, skor Early Warning Score (EWS) saat masuk dan keluar, serta efektivitas intervensi CCOT berdasarkan stabilitas pasien, kebutuhan masuk ICU ulang, kejadian code blue, dan kematian. Hasil penelitian mendapatkan dari 136 pasien yang dipantau, persentase tertinggi 30,8% di usia 56-65 tahun dan memiliki skor EWS sedang hingga tinggi saat masuk. Setelah intervensi CCOT, terjadi penurunan skor EWS rerata dari 5,9 menjadi 4,5. Sebanyak 94,1% pasien tetap stabil di bangsal, 3,7% kembali ke ICU, 1,5% mengalami code blue, dan 0,7% meninggal. Simpulan penelitian ini ialah implementasi CCOT di rumah sakit ini telah berjalan dengan baik dalam mendeteksi dini kemunduran kondisi pasien dan memberikan intervensi yang tepat waktu, sehingga meningkatkan keselamatan dan efisiensi pelayanan. Kata kunci: Early Warning Score; Rapid Response System; Critical Care Outreach Team (CCOT); kemunduran kondisi; intervensi dini